2001
DOI: 10.1002/j.2161-007x.2001.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Spiritual Issues in Secular Psychotherapy

Abstract: The author discusses spirituality as a human phenomenon that is independent of, yet open to, matters of personal religion and belief in God. Although commonly expressed through religion and theist belief, the author views spirituality as a universal mental phenomenon with an inherent “normativity”; it can, therefore, be legitimately addressed as a prescriptive aspect of psychology apart from theology and religion. An elaborated psychology of spirituality helps therapists focus the psychotherapeutically relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 50 publications
1
71
0
3
Order By: Relevance
“…A minority of professionals might consider religious or spiritual concerns to be neurotic, infantile, or secondary (Miller, 2003). We concur with Helminiak's (2001) view that ignoring spiritual issues in counselor training may facilitate insensitivity by a counselor to clients' religious and spiritual concerns.…”
Section: Professional Identity Core Areasupporting
confidence: 83%
See 1 more Smart Citation
“…A minority of professionals might consider religious or spiritual concerns to be neurotic, infantile, or secondary (Miller, 2003). We concur with Helminiak's (2001) view that ignoring spiritual issues in counselor training may facilitate insensitivity by a counselor to clients' religious and spiritual concerns.…”
Section: Professional Identity Core Areasupporting
confidence: 83%
“…Reading resources include sources that address issues of helping skills and spirituality and working with populations that are diverse in age, gender, ethnicity, race, sexual orientation, and religious background. Resources that we have used that others might find helpful include Burke and Miranti (1995), Fukuyama and Sevig (1999), Garrett (1999), Helminiak (2001), Ingersoll (1994), Miller (2003, and Myers et al (2000). Such readings can provide specific information, training, and intervention strategies for addressing spiritual issues in helping relationships.…”
Section: Helping Relationships Core Areamentioning
confidence: 91%
“…Although some researchers have argued that religion and spirituality could be distinct concepts (Del Rio & White, 2012;Helminiak, 2001;Legere, 1984), many have argued that seeing them as separate can cause problems in operationalizing their definitions (Hill et al, 2000;Smith, 2007). Selvam (2013) suggested that viewing these two concepts as separate is particularly predominant in Western cultures; in other cultures, the concepts of religion and spirituality are the same.…”
Section: Religion and Spiritualitymentioning
confidence: 99%
“…It is also a way to build a religious community, which provides social support (Burkhart & Solari-Twadell, 2001;Hummer, Rogers, Nam, & Ellison, 1999;Smith, 2007;Zinnbauer & Pargament, 2013). Spirituality, on the other hand, is often thought of as a private and individual experience (Helminiak, 2001;Richards & Bergin, 1997). This may lead to people not associating spirituality with attending church.…”
Section: Values and Characteristics People Expect Of Religious And Spmentioning
confidence: 99%
See 1 more Smart Citation